Development of ecological tourism in Ukraine - I.V.; D.R. (Економіка, управління та адміністрування, 2023)
Ukraine has a powerful natural potential and a rich natural heritage, but pollution and neglect of natural resources in recent decades have caused a significant deterioration of the environment. Therefore, it is important to actively work on reducing environmental damage and restoring destroyed ecosystems. The development of ecotourism can have both positive and negative consequences for the environment. On the one hand, ecotourism can contribute to the preservation of natural complexes by raising the awareness of tourists about the need to protect the environment, as well as by creating financial resources for the preservation of natural areas. On the other hand, tourism can lead to deterioration of the quality of the environment through air, water and land pollution, degradation of soils and forests, destruction of rare species of animals and plants. To ensure the sustainable development of ecotourism, approaches to its organization are proposed that will contribute to the preservation of natural areas and the reduction of negative impact on the environment (in particular, the development and implementation of environmental policy by the subjects of tourist activity, the preservation of natural, social and cultural diversity, increasing the level of environmental education of visitors, promotion of minimization of pollution, elimination of excessive consumption of resources), as well as regional economic and social development of the country. Further research should be aimed at identifying and evaluating the impact of different forms of tourism on natural complexes, such as mass tourism and tourism in extreme conditions. Research should also consider various factors influencing tourists’ environmental attitudes and behavior in natural areas. One of the promising directions is research into the use of new technologies, such as drones and satellite images, to monitor natural areas and assess the impact of tourism on natural complexes.